2004
DOI: 10.1093/ndt/gfh237
|View full text |Cite
|
Sign up to set email alerts
|

The haemodynamic response to submaximal exercise during isovolaemic haemodialysis

Abstract: The haemodynamic response to exercise during haemodialysis is comparable with that in normal individuals. The rapid reduction in RBV on exercise occurs in spite of a significant increase in CO, mainly as a consequence of fluid shifts from the microvasculature to the interstitium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
4
13
0
3
Order By: Relevance
“…Other studies have also observed an increase in SBP during a bout of intradialytic exercise from as little as 10 min duration [30,31,32]. These studies concluded that exercise during HD is met with a stable haemodynamic response; the cardiovascular response to exercise is normal and superimposed onto the response to HD.…”
Section: Discussionmentioning
confidence: 85%
“…Other studies have also observed an increase in SBP during a bout of intradialytic exercise from as little as 10 min duration [30,31,32]. These studies concluded that exercise during HD is met with a stable haemodynamic response; the cardiovascular response to exercise is normal and superimposed onto the response to HD.…”
Section: Discussionmentioning
confidence: 85%
“…For intradialytic exercise, it is safer to train during the first 2 h of the HD session because, after 2 h of dialysis, shifting of fluid from the microvasculature to the interstitium during exercise can cause a rapid reduction in relative blood volume [87] with accompanying cardiovascular decompensation which may preclude further exercise. …”
Section: Practical Methods For Applying Exercise Therapymentioning
confidence: 99%
“…Monitored plasma protein concentrations would not change if this were the sole effect of food intake. Alternatively, food-induced fluid translocation from the microcirculation to the interstitium would lead to a rise in both haematocrit and plasma protein concentrations [8] . We used continuous segmental bioimpedance (CSBI) techniques to track changes in extracellular fluid (ECF) resistance during HD [9] , and non-invasively tracked CO by a thoracic bioimpedance technique, the findings of which correlate well with those of conventional thermodilution [10] .…”
Section: Introductionmentioning
confidence: 99%